2021
DOI: 10.1002/adom.202100227
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of UV Photoelectron Spectroscopy on the Field of Organic Optoelectronics—A Retrospective

Abstract: The field of organic electronics has been of widespread interest for a long time. Over the years, device efficiencies increased steadily due to the development of new materials, as well as an improved understanding of the physical mechanisms governing underlying fundamental processes such as charge transport or charge carrier generation and recombination. Especially the positions of energy levels that are responsible for the charge transport throughout a device are of paramount importance. This generated a hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 206 publications
(399 reference statements)
2
15
0
Order By: Relevance
“…The energy level alignment at organic/organic as well as organic/metal oxide interfaces has already been studied extensively in the past, uncovering the electronic state interplay in such systems, including studies of such interfaces in organic electronic devices and OSCs. , Even though the energy level alignment in organic heterojunctions has been studied for other systems, the DBP/4P-NPD interface remains particularly interesting from a device point of view, since only devices with ultrathin 4P-NPD layers (0.7 and 1 nm) experience an improvement in device performance, while devices with thicker 4P-NPD layers (5 nm and above) experience a decrease in performance compared to reference devices . We demonstrate the presence of a negative HOMO offset between the thick 4P-NPD layer and DBP donor layer that explains the poor device performance.…”
Section: Introductionmentioning
confidence: 99%
“…The energy level alignment at organic/organic as well as organic/metal oxide interfaces has already been studied extensively in the past, uncovering the electronic state interplay in such systems, including studies of such interfaces in organic electronic devices and OSCs. , Even though the energy level alignment in organic heterojunctions has been studied for other systems, the DBP/4P-NPD interface remains particularly interesting from a device point of view, since only devices with ultrathin 4P-NPD layers (0.7 and 1 nm) experience an improvement in device performance, while devices with thicker 4P-NPD layers (5 nm and above) experience a decrease in performance compared to reference devices . We demonstrate the presence of a negative HOMO offset between the thick 4P-NPD layer and DBP donor layer that explains the poor device performance.…”
Section: Introductionmentioning
confidence: 99%
“…The binding energy (BE) was calibrated by using the Fermi-edge of a freshly sputtered Au(111) sample. Charge compensation was not performed as sample charging is usually not an issue for XPS and UPS measurements for organic semiconductor thin films with thicknesses up to several hundred Å [13] and was, indeed, not observed for 6 T thin films [27,35]. All preparation steps and measurements were performed at room temperature (295 K).…”
Section: Methodsmentioning
confidence: 99%
“…IEs of organic thin films and ELA at organic-inorganic interfaces can be experimentally accessed by ultraviolet photoelectron spectroscopy (UPS) [7,11,12]. Furthermore, UPS can be used to access structural properties of organic thin films [13]: Disorder leads to a broadening of HOMO-derived photoemission intensity [14,15] and the IE differs by around 0.5 eV for thin films of most rodlike molecules in a lying and a standing orientation [16,17]. Band bending in the inorganic semiconductor can be tracked by core-level shifts, which can be measured by x-ray photoelectron spectroscopy (XPS) [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…The observed dependence of V OC on the concentration of the third component has been attributed to either the heterojunction interface or to bulk recombination. For low third component concentrations, the V OC variation has been usually attributed to an interfacial effect. , This phenomenon has been usually studied using optical methods such as photoluminescence and absorbance to calculate interfacial energies. However, such interfacial energies or charge-transfer states are difficult to detect using conventional techniques relying on transmission and reflection measurements and are applied to the main junction of the device without contacts, which, in some cases, can determine its V OC . In the present study, it is shown for the first time that the typically observed V OC tuning effect in TSCs with a low third-component concentration can be understood using simple electrical characterization, that is, the thermal analysis of the current density–voltage ( J – V ) characteristics of the complete device under dark conditions.…”
Section: Introductionmentioning
confidence: 99%